2023
DOI: 10.1002/lpor.202200832
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed Self‐Reduction of Manganese in Mg2SnO4 via Li+ Incorporation with Polychromatic Luminescence for Versatile Applications

Abstract: Herein, the self‐reduction behavior of manganese (Mn) in Mg2SnO4 (MSO) host lattices prepared by using the solid‐state reaction technique in air atmosphere is reported. Excited by 282 nm, only the emission of Mn2+ is seen, and the observed results are confirmed by theoretical calculation based on the density functional theory. Noteworthy, with the codoping of Li+, the self‐reduction process of Mn is suppressed, leading to the coexistence of Mn2+ and Mn4+ in MSO host lattices along with the multicolor emissions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…The well-resolved sextet hyperfine lines were ascribed to the interaction between the electron spin and nuclear spin of isolated Mn 2+ ions at the low doping level of x = 0.01. 50,51 However, the EPR spectra consisted of a singlet structure for x = 0.1 and 0.3, and there was less splitting of the sextet hyperfine lines compared to that of the isolated Mn 2+ ions due to the spin-relaxation processes in the exchange coupling of Mn 2+ ions. 52,53 This further demonstrated that the red emission in the LZPO: x Mn 2+ system originated from the isolated Mn 2+ ions and Mn 2+ –Mn 2+ dimers.…”
Section: Resultsmentioning
confidence: 94%
“…The well-resolved sextet hyperfine lines were ascribed to the interaction between the electron spin and nuclear spin of isolated Mn 2+ ions at the low doping level of x = 0.01. 50,51 However, the EPR spectra consisted of a singlet structure for x = 0.1 and 0.3, and there was less splitting of the sextet hyperfine lines compared to that of the isolated Mn 2+ ions due to the spin-relaxation processes in the exchange coupling of Mn 2+ ions. 52,53 This further demonstrated that the red emission in the LZPO: x Mn 2+ system originated from the isolated Mn 2+ ions and Mn 2+ –Mn 2+ dimers.…”
Section: Resultsmentioning
confidence: 94%
“…In the examples of non-equivalent substitution of host cations, Li + ions are commonly chosen, with a few cases involving other cations. 17 As mentioned earlier, the non-equivalent occupation of the Ca 2+ site by Mn 4+ in the CSO host is the main cause of self-reduction. Meanwhile, compared to Mn 2+ and Mn 4+ , the La 3+ ion has a closer radius to Ca 2+ and also undergoes non-equivalent substitution for Ca 2+ .…”
Section: Inhibition Of Self-reduction Of Mnmentioning
confidence: 86%
“…Obviously, the S a and S r values obtained are different, which indicates that the temperature measurement performance of the developed optical temperature sensor can be adjusted by changing the excitation wavelength. 17 Alternatively, the doping concentration of La 3+ also has an effect on the temperature sensing capacity. Under the same 310 nm excitation, the maximum S a value for the CSO:0.01Mn,0.04La 3+ phosphor was 0.048 K −1 at 440 K, and the maximum S r value was 2.78% K −1 at 420 K, which are different from the maximum S a and S r values of the CSO:0.01Mn,0.02La 3+ phosphor samples, respect-ively.…”
Section: Optical Temperature Sensor Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the optical properties, several authors have already demonstrated that Mg 2 SnO 4 has diverse applications, such as dielectric material for microwave devices 1 , electronic ceramics 15 , wireless high-temperature sensor 16 , field emission displays (FEDs) 17 , self-sustainable night vision devices 10 , Liion battery electrodes (when combined with SnO 2 ) 18 , probe in autofluorescence bioimaging 11 , fingerprint visualization 19 and optical storage 8 .…”
Section: Introductionmentioning
confidence: 99%